Analysis of CAPZA3 localization reveals temporally discrete events during the acrosome reaction - Sosnik, Julian (2010)
In mammals, the starting point of development is the fusion between sperm and egg. It is well established that sperm fuse with the egg through the equatorial/post-acrosomal region. Apart from this observation and the requirement of two proteins (CD9 in the egg and IZUMO1 in the sperm) very little is known about this fundamental process. Actin polymerization correlates with sperm capacitation in different mammalian species and it has been proposed that F-actin breakdown is needed during the acrosome reaction. Recently, we have presented evidence that actin polymerization inhibitors block the movement of IZUMO1 that accompany the acrosome reaction. These results suggest that actin dynamics play a role in the observed changes in IZUMO1 localization. This finding is significant because IZUMO1 localization in acrosome-intact sperm is not compatible with the known location of the initiation of the fusion between the sperm and the egg. To further understand the actin-mediated changes in protein localization during the acrosome reaction, the distribution of the sperm- specific plus-end actin capping protein CAPZA3 was analyzed. Like IZUMO1, CAPZA3 shows a dynamic pattern of localization; however, these movements follow a different temporal pattern than the changes observed with IZUMO1. In addition, the actin polymerization inhibitor latrunculin A was unable to alter CAPZA3 movement.